The associations of board of directors’ characteristics with modified audit opinion (2020)
The aim of this study is to investigate the association between the characteristics of the board of directors and the likelihood that a company receives a modified audit opinion (as a measure of the quality of companies external financial reporting) in Malaysia. To test our hypotheses, we use the pooled cross-sectional logistic regression analysis for 136 firm-year observations listed on Bursa Malaysia over the period 2009-2011.The evidence we uncover is consistent with the hypotheses that companies with large board size and greater financial expertise of the board of directors are less possible to receive a modified audit opinion. The evidence offers by this study reinforces the listing rules of the Malaysian-Corporate-Governance Code and the requirements of the Bursa Malaysia Corporate-Governance-Guide, which consider the significance of the board of directors as an aspect of good corporate governance to its critical role in the Malaysian financial reporting process.